Feasibility Study with Emphasis on the Financial Aspect for Establishing A Middle Scale Biodiesel Industry by The Use of VCO Industry Waste - Nugroho, Wahyunanto Agung; Nurhidayah, Titik; Ahmad, Ary Mustofa (Jurnal Teknologi Pertanian, 2006)
The objective of this research is to do a feasibility study with an emphasis on the financial aspect of the establishment of a middle scale industry if VCO as a primary product and biodiesel as a secondary product. The results indicated that the gross price for biodiesel is RP. 1754.43 and Rp. 7752.13 for VCO. BEP will be achieved at the production of 4655.3 liter of VCO and 2880.28 liter of biodiesel and a payback period of 11 months. The values of BC ratio, NPV and IRR were 4.71, Rp. 6680356346.00 and 259.24%, respectively and therefore the establishment of the industry was feasible. Keywords:Â VCO waste, biodiesel, feasibility study, industry